Performance analysis of a node monitoring protocol for mobile ad–hoc networks: an agent–based approach. (10th April 2015) - Channappagoudar, Mallikarjun B.; Venkataram, Pallapa
In network management, monitoring the nodes of a network is considered as an important and crucial process to have both the network and applications work properly. The complexity of node monitoring in mobile ad–hoc networks (MANETs) increases further due to its dynamic network topology. The scarcity of resources and nodes' random movement lead to a challenge in monitoring the nodes in a MANET. Monitoring the lack of resources (bandwidth, buffer, and energy), misbehaviour, and mobility, at a node level remains as another challenge. We have proposed a monitoring protocol for MANETs, which uses both static as well as mobile agents. In this work, we have extended our protocol, to monitor the gradational energy loss of nodes running with low to high load of mobile applications. We have also studied the performance of the protocol analytically. The protocol functionality has been simulated using Java Agent Development Environment (JADE) framework for agent generation, migration and communication. The protocol has been tested on different MANETs with variable number of nodes and applications. Performance analysis and simulation of the proposed system represents the effectiveness of the protocol. We have compared our proposed work with other techniques, which shows the improvement over certain techniques in terms of network overhead and response time.